Pengembangan Media Angel Path pada Bimbingan dan Konseling - Angelina, Putri Ria; Dewi, Reni Sinta; Hamidah, Rizka Nur; Haerani, Naila (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
The research aims to find out how to develop Angel Path media in career guidance and counseling to increase students' career maturity. This research uses the research and development method which refers to Borg and Gall (1998), from 10 stages the researcher uses 5 stages to adjust research needs with the following steps: (1) Identification of Potential and Problems, (2) Data Collection, (3) ) Product Design, (4) Product Validation, (5) Product Revision. The results of this research can be seen from the results of validation by three experts, namely one guidance and counseling teacher who is currently studying a master's degree in guidance and counseling, one expert in the field of media who is currently studying a master's degree in educational psychology, and one student who has used Angel media. The path with the results of the quality assessment of the feasibility of the product being developed is included in the